2012
DOI: 10.5402/2012/573826
|View full text |Cite
|
Sign up to set email alerts
|

Wagner's Law in Sri Lanka: An Econometric Analysis

Abstract: This study examines whether there is empirical evidence that Wagner's law holds in the Sri Lankan economy using time series annual data over the period from 1960 to 2010 for Sri Lanka, applying cointegration and error correction modeling (ECM) techniques. In particular, this study keeps a special focus to examine the validity of six versions of Wagner's hypothesis, which support the existence of long-run relationship between public expenditure and economic growth. The empirical evidence of this study indicates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
(14 reference statements)
1
8
1
Order By: Relevance
“…As it is shown from the result, with rising level of economic growth, the country will likely increase its public investment which clearly related to an evolving demand for goods and services produced by the public sector. This result is in line findings of earlier produced research papers like Richter and Paparas (2012), Kesavarajah (2012), Aregbeyen and Akpan (2013), and Obeng and Sakyi (2017). Another variable that shows positive relationship with public investment is private investment and shows that private investment and government capital spending are moving in tandem.…”
Section: Plot Of Cumulative Sum Of Squares Of Recursive Residualssupporting
confidence: 91%
“…As it is shown from the result, with rising level of economic growth, the country will likely increase its public investment which clearly related to an evolving demand for goods and services produced by the public sector. This result is in line findings of earlier produced research papers like Richter and Paparas (2012), Kesavarajah (2012), Aregbeyen and Akpan (2013), and Obeng and Sakyi (2017). Another variable that shows positive relationship with public investment is private investment and shows that private investment and government capital spending are moving in tandem.…”
Section: Plot Of Cumulative Sum Of Squares Of Recursive Residualssupporting
confidence: 91%
“…This indicates that Wagner's Law is not supported and that the law is not a reality but an ordinary myth in Nigeria during the period under investigation. The result of the study conforms with those of Kesavarajah (2012) and Owolabi (2015) but conflicts with the findings of Aniefiok and Charles (2014) and Tsenba and Gushibet (2016). The study recommends that government should put appropriate fiscal policy in place in order to increase government expenditure for attaining economic growth objective in Nigeria.…”
Section: Conclusion and Policy Recommendationscontrasting
confidence: 49%
“…investigated the validity of Wagner's law for United States over the period of 1957-2006. By using disaggregated expenditure measures, the study found that total expenditure, insurance trust benefits, social services are co integrated with national income in long run Kesavarajah (2012). studied the Wagner's law for Sri Lanka period from 1960 to 2010 and found validity of Wagner's law only in the short run Moore (2016).…”
mentioning
confidence: 99%